MODELING OF THE WORKING MECHANISM OF THE TRUCK DRYER SYSTEM 130 PS IN SIMULINK-BASED OVERLOAD CONDITIONS - Herawati Indah; Dede Lia Zariatin (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2026)
In  the automotive industry, various improvements in  the  quality of vehicles continue  to  be  carried  out  in  terms  of  safety,  comfort,  convenience, beauty,  and  consumer confidence as the users of the vehicle itself.  One of the system that plays an important role in vehicles is the braking system which stops the vehicle's speed. In this case study, a brake oil leak was found in a 130 PS truck which could have a dangerous effect on the braking system.  After being analyzed in the field, the wheel cylinder on the brake component breaks down due to user behavior, which is the overload and the incorrect timing of the brake adjustment.  Improvements in terms of design are still being done and tested until now at PT.HMMI. One of the methods to determine the performance of the braking system is dynamic modeling.   In this study an analysis of vehicle forces during braking is done by emphasizing the slip until the tire stops. This modeling uses software simulation that compares the time and distance on the brake pedal.  Restores force or approved stop wheels for ABS (Antilock Braking System) and LBS (Lock Braking System) if applied to a 130 PS truck. From the results of the analysis and assessment of the simulation it was concluded that the ABS system has shorter time and distance values compared to LBS.   It is expected that by modeling this braking system it will be used as a reference during the initial design so as to reduce the risk of component failures that can endanger the truck users and material losses